2014
DOI: 10.1007/s00404-014-3479-y
|View full text |Cite
|
Sign up to set email alerts
|

Strain elastography in placental dysfunction: placental elasticity differences in normal and preeclamptic pregnancies in the second trimester

Abstract: The placental elasticity ratios measured by SE imaging during the second trimester differ between the normal pregnancies and the pregnancies complicated by PE. SE might be used as a supplement tool in addition to the existing methods for the prediction of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 34 publications
(52 reference statements)
0
42
0
1
Order By: Relevance
“…There have been limited studies concerning ARFI investigating placental elasticity [17][18][19]. Sugitani et al [13] measured the placental elasticity by using ARFI in an ex vivo study and they found higher ARFI scores in intrauterine growth restricted and hypertensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been limited studies concerning ARFI investigating placental elasticity [17][18][19]. Sugitani et al [13] measured the placental elasticity by using ARFI in an ex vivo study and they found higher ARFI scores in intrauterine growth restricted and hypertensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Sugitani et al [13] measured the placental elasticity by using ARFI in an ex vivo study and they found higher ARFI scores in intrauterine growth restricted and hypertensive pregnancies. Recent in vivo studies demonstrated that the placenta becomes stiffer in preeclamptic pregnancies [17][18][19]. Placental infarction, inflammation of trophoblastic villi and vasculitis are major findings which occur in intrauterine growth restricted and hypertensive pregnancies [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In obstetrics and gynaecology, elastography has been used to assess uterine fibroids, subchorionic hematoma, and cervical length in the cases of preterm labour [1618]. It has also more recently been used to evaluate differences in placental function between normal and preeclamptic pregnancies and may be useful as an aid in predicting preeclampsia [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…We thank Dr. Canan Cimsit for prompting a rigorous re-evaluation of our manuscript (Lau et al, 2015), specifically on our interpretation of Cimsit et al (2015) in our introduction and discussion sections. Like Dr. Cimsit, we believe and support rigorous discussion and exchanges.…”
Section: Conflict Of Interestmentioning
confidence: 98%